Redução na população de plantas sobre a produtividade e a qualidade fisiológica da semente de soja - Vazquez, Gisele Herbst [UNESP]; Carvalho, Nelson Moreira de [UNESP]; Borba, Maria Madalena Zocoller [UNESP] (Associação Brasileira de Tecnologia de Sementes (ABRATES), 2008)
O objetivo deste trabalho foi avaliar os efeitos de reduções na população de plantas sobre a produtividade e a qualidade fisiológica da semente de soja. Duas cultivares de soja (BRSMG 68 Vencedora e M-SOY 8001) foram cultivadas em áreas com e sem o controle de plantas daninhas. As populações estudadas foram: 400.000, 340.000, 280.000, 220.000 e 160.000 pl.ha-1, em um espaçamento entrelinhas de 0,43m. de maneira geral, a presença de plantas daninhas causa decréscimos na produtividade e no tamanho da semente produzida. Entretanto, variações na população não interferem na qualidade fisiológica, no tamanho e na massa de 100 sementes. A cultura da soja é capaz de suportar grandes reduções de população sem perdas significativas de produtividade. Essa capacidade é grandemente influenciável pela cultivar: a Vencedora suporta reduções de até 45% e a M-SOY 8001 de até 30%, em relação à população de 400.000 pl.ha-1.

The effects of plant population reductions on soybean plant yield and seed physiological quality were studied. Two soybean cultivars [BRSMG 68 (a.k.a. 'Vencedora') and M-SOY 8001] were grown in areas with and without weed control. The population of 400,000 plants/hectare was assumed as the referential population and the other treatments consisted of populations of 340,000, 280,000, 220,000, and 160,000 plants/hectare, that is, the referential population reduced by 15, 30, 45, and 60%, respectively. When applicable, herbicides were used to control weeds. The presence of weeds reduced yield and seed size. Plant population reductions did not interfere in the seed physiological quality, seed size and weight of 100 seeds. Soybean was found to withstand great population reductions without significant reductions in yield. This performance was found to be highly influenced by the genotype: 'Vencedora' withstood up to 45% and the M-SOY 8001 up to 30% plant population reductions without significant loss in productivity.
Effects of plant population reductions on yield and seed physiological quality of soybeans
Keywords: stand; Seed vigor; cultural control; weed control; Glycine max; estande; Vigor; Controle cultural; Plantas daninhas; Glycine max